Economic Analysis of Climate Change Best Management Practices in Vermont Agriculture - Alexander P. Helling (Agriculture, 2015)
Climate change impacts local agricultural systems in detectable and distinguishable ways from large-scale shifts in water, land, and weather patterns to regionally specific distributions of weeds, pests, and diseases. Best management practices for adapting to and mitigating the effects of climate change include modifications to farm production through adjusted intensity and product types and changing land use through crop siting and tillage practices. Farmer perceptions of risk and profitability of best management practices are key determinants of adoption, which traditional incentive programs like the Environmental Quality Incentive Program attempt to address by providing financial and technical support. To ensure that payments offered through these programs that maximize adoption, regional incentive payments must be based upon locally established costs. This paper focuses on the cost of implementing and maintaining climate change specific best management practices (CCBMPs) for twelve diverse farms in Vermont. Specifically, three CCBMPs for Vermont are examined: cover cropping, management intensive rotational grazing (MIRG), and riparian buffer strips. Results show the average cost for cover cropping is $129.24/acre, MIRG is $79.82/acre, and a tree based riparian buffer strip cost $807.33/acre. We conclude that existing incentive payments for cover cropping and MIRG are below costs, likely resulting in under-adoption.